ADAPTASI PSIKOLOGIS IBU HAMIL DALAM PENCAPAIAN PERAN SEBAGAI IBU DI PUSKESMAS KEMBARAN II KABUPATEN BANYUMAS - Wilis Dwi Pangesti (Universitas Harapan Bangsa Purwokerto, 2018)
Pregnancy is a physiological and normal process, not only relates with the biological aspect but also relates to the social, cultural, psychological, emotional, and spiritual aspects of a woman in life. A woman has a task to attain the role of a mother during her pregnancy. There are three stages of adaptation to achieve the role of mother based on trimester of pregnancy. This research aims to describe the physiological adaptation of pregnant women in achieving the role as a mother in the Kembaran II health centre of Banyumas. It is a qualitative research with case study research design. Research subject taken by purposive sampling. The main subject consists of 8 pregnant womens, while the supporting subject is the husband of 8 pregnant womens and 4 midwives in around the research area. Source of research data is the primary data using interview compass. Data analysis using a qualitative analysis techniques with Milles and Huberman's interactive analysis models. The results of this research can be concluded that all of pregnant women in Kembaran II health centre of Banyumas has achieved its role as a mother according to the stage in her pregnancy trimester. There is one condition where pregnant women receive her fetus too early in theﬁrst trimester of pregnancy by just looking at the results of a pregnancy test, it's different with previous theory.Keywords: Psychological Adaptation, Pregnancy, Achievement of mother role